Pengukuran Usability Aplikasi SIM (Sistem Integrasi Mitra) Menggunakan Metode Use Questionnaire - Yasmin Rosana; Wafiah Murniati (Lembaga Pengembangan Kinerja Dosen, 2025)
Usability evaluation is a crucial element in assessing the quality of an application, especially from the end-user perspective. This study aims to evaluate the level of usability of the SIM (Partner Integration System) application, which functions as a means of managing company partnership data and services. The approach used is the USE Questionnaire method, which includes four main aspects: usefulness, ease of use, ease of learning, and satisfaction. Data was collected through a questionnaire filled out by active users of the SIM application. The measurement results show that the application has an average usability value of 81.09%, which is categorized as a very good level. The usefulness and ease of use dimensions obtained the highest scores of 87.00% and 85.14%, respectively, indicating that the application is considered very useful and easy to use. Meanwhile, the Ease of Learning and Satisfaction dimensions scored 72.67% and 79.56%, respectively, indicating potential for improvement, particularly in the learning and user satisfaction aspects. These findings provide important insights for developers in improving quality and user experience.